The Indonesian Crisis: A Structural View - Hastu Prabatmodjo (Journal of Regional and City Planning, 1998)
The financial crisis starting from July 1997 has become an unparalleled problem for the New Order government, leading to its down falL Before the crisis, Indonesia did not have a reliable regime of accumulation. At the same time, rapid engagement with globalization was not accompanied by adjustments in modes of regulation. External and internal factors have contributed to the current crisis which cannot be resolved without a ma/or overhaul in the national system. It requires total changes in the paradigm and culture.